2007 4th IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2007
DOI: 10.1109/isbi.2007.356845
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Image Analysis Toolbox for High-Throughput Drosophila Embryo Rnai Screens

Abstract: We build an image analysis toolbox for high-throughput Drosophila embryo RNAi screens. The goal is to tag the embryo as normal, developmentally delayed or abnormal based on the ventral furrow formation. We break the problem into two parts: in the first, we detect the developmental stage based on the progress of the ventral furrow formation, and in the second, we tag the embryo as normal/developmentally delayed/abnormal based on the stage detected and the elapsed time. The crux of the algorithm is the multireso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…MRC is a supervised classification framework (see Figure 2), originally proposed for bioimaging applications [4,7,8]. It decomposes images into S localized space-frequency subbands using wavelet packets, a data-adaptive MR technique [9].…”
Section: Background and Problem Formulationmentioning
confidence: 99%
“…MRC is a supervised classification framework (see Figure 2), originally proposed for bioimaging applications [4,7,8]. It decomposes images into S localized space-frequency subbands using wavelet packets, a data-adaptive MR technique [9].…”
Section: Background and Problem Formulationmentioning
confidence: 99%
“…Redundancy often leads to increased accuracy, as has been found in a host of bioimaging problems (see Chebira & Kovačević 2008a and references therein). One possible example of the power of multiresolution techniques in pattern classification is that developed for the classification of Drosophila embryo development (Kellogg et al 2007). Using a highly accurate multiresolution classification algorithm developed by Kovačević and her group, the process is now automated and reproducible, with accuracy greater than 98% (Kellogg et al 2007).…”
Section: Multiresolution Classificationmentioning
confidence: 99%
“…2). This system has proven accurate for various classification tasks [5,4,6,7]; we now briefly describe it. Multiresolution Block.…”
Section: Adaptive Multiresolution Classificationmentioning
confidence: 99%
“…In our previous work [5,4,6,7], we found that classifying in multiresolution (MR) subspaces adds to the discriminative power of a classification system. Moreover, based on our previous experience, modified Haralick texture features [4] (our improvement of the known Haralick texture features), were typically sufficient for high classification accuracies on those data sets (in the mid to upper 90s).…”
Section: Introductionmentioning
confidence: 99%